Mutations in NBAS and SCYL1, genetic causes of recurrent liver failure in children: Three case reports and a literature review - Chavany, J.; Cano, A.; Roquelaure, B.; Bourgeois, P.; Boubnova, J.; Gaignard, P.; Hoebeke, C.; Reynaud, R.; Rhomer, B.; Slama, A.; Badens, C.; Chabrol, B.; et al. (Archives de pédiatrie : organe officiel de la Société française de pédiatrie, 2020)
Acute liver failure (ALF) in childhood is a life-threatening emergency. ALF is often caused by drug toxicity, autoimmune hepatitis, inherited metabolic diseases, and infections. However, despite thorough investigations, a cause cannot be determined in approximately 50% of cases. Here, we report three cases with recurrent ALF caused by NBAS and SCYL1 pathogenic variants. These patients did not present with any other phenotypic sign usually associated with NBAS and SCYL1 pathogenic variants. Two of them underwent liver transplantation and are healthy without recurrence of ALF. We propose NBAS and SCYL1 genetic analysis in children with unexplained fever-triggered recurrent ALF even without a typical phenotype.